Lotus seed (Nelumbinis semen) extract: anticancer potential and chemoprofiling by in vitro, in silico and GC-MS studies - Mallela, Vijaya Jyothi; Rudrapal, Mithun; Prasanth, D. S. N. B. K.; Pasala, Praveen Kumar; Bendale, Atul R.; Bhattacharya, Soumya; Aldosari, Sahar M.; Khan, Johra (Frontiers in Chemistry, 2024)
Lotus seeds, also known as Nelumbinis semen, has been utilized for over 7,000 years as vegetable, functional food and medicine. In this study, we primarily investigated the anticancer effects of lotus seed extracts, particularly of the methanolic extract (MELS) on cell proliferation inhibition, apoptosis induction and cell cycle arrest in ovarian cancer cell lines. Further, we studied the phytochemical composition of the MELS by gas chromatography-mass spectrometry (GC-MS) analysis. Additionally, molecular docking was performed in order to substantiate the in vitro anticancer effect by in silico inhibitory study of human survivin protein. Our in vitro study demonstrated significant inhibition of SKOV3 (IC50: 79.73 ± 0.91), A2780 (IC50: 100.18 ± 2.42), SKOV3-CisR (IC50: 115.87 ± 2.2) and A2780-CisR (IC50: 138.86 ± 2.46) cells by MELS, compared to acetone, petroleum ether, n-hexane extracts, and the standard drug, cisplatin. Furthermore, MELS resulted in a substantial increase in apoptosis cell count to 78% in A2780-CisR cells and 82% in SKOV3-CisR cells, whereas a significant reduction in the G1 and G2/M phases of cells treated with MELS when compared to the control group. To identify the potential phytocompounds present in the MELS, we conducted GC-MS analysis, which led to the identification of 14 compounds. Molecular docking analysis revealed that oleic acid, stigmast-5-en-3-ol, phytol and glyceryl linolenate exhibited remarkable binding affinities of −6.1, −5.9, −5.8 and −5.6 kcal/mol, respectively against survivin. Our findings suggest that certain phytochemicals presented above found in MELS may have therapeutic potential for management of ovarian cancer.